Distribution of Tunisian beet wild relatives (Beta sp.) according to morphological characteristics and eco-geographical origin - Kaouther Ben Mahmoud; Najla Mezghani; Youssef Ouakrim; Neila Mezghani; Noura Jemai; Ahmed Jemmali (Heliyon)
Beta vulgaris subsp. maritima (L.) Arcang. and Beta macrocarpa Guss. are crop wild relative taxa belonging to the primary gene pool. They constitute a crucial gene reserve for enhancing cultivated Beta species (B. vulgaris subsp. vulgaris L.). Climate change poses a significant threat to genetic reservoir in Tunisia. We evaluated the morphological diversity of ten populations of B. vulgaris subsp. maritima and five populations of B. macrocarpa growing in different Tunisian bioclimatic and ecological areas using a set of 9 quantitative and 14 qualitative traits to promote the preservation and exploration of this germplasm. Variance component analysis of the quantitative data showed an important spectrum of variability, both within and between populations. The principal component analysis (PCA) allocated this wild Beta collection into three groups. G1 included the populations of B. macrocarpa that were characterized by the largest glomerules and heaviest seeds, while G2 included all B. vulgaris subsp. maritima populations except one, i.e., N1015 that clustered into G3, which was characterized by the highest values of leaf characters. Similarly, qualitative traits exhibited a high diversity level (H'index ≥0.6) for almost all characters. The PCA divided these 15 populations into three groups as well: G′1 concerned the island B. vulgaris subsp. maritima populations, characterized by prostrate growth habit and red inflorescences; G′2 included all B. macrocarpa populations characterized by erect-procumbent growth habit and very synchronous flowering pattern; and G′3 was formed by the mainland B. vulgaris subsp. maritima populations, characterized by erect growth habit and hairy, curly leaves. The observed eco-geographic distribution patterns suggest that these wild relatives are highly adaptable to diverse and even extreme conditions (salinity, heat, and drought), highlighting their potential as resilient gene sources for beet breeding under the challenges of accelerating climate change.